A novel oxime-derived 3d–4f single-molecule magnet exhibiting two single-ion magnetic relaxations. Issue 29 (5th July 2016) - Dong, Hui-Ming; Li, Yan; Liu, Zhong-Yi; Yang, En-Cui; Zhao, Xiao-Jun
Abstract : A weak ferromagnetic coupled Dy4 Ni6 cluster with a butterfly-shaped DyIII4 core and four-coordinate diamagnetic Ni II ions shows field-induced SMM behaviour with two overlapping thermally activated relaxations. Abstract : A new oxime-derived DyIII4NiII6 cluster with a paramagnetic butterfly-shaped DyIII4 core and peripheral diamagnetic planar-square Ni II ions was solvothermally synthesized. The weak ferromagnetically coupled cluster exhibits field-induced single-molecule magnetic behavior with two thermally activated single-ion relaxations.